DETECTION AND QUANTITATION OF RED COMPLEX BACTERIA IN SUBGINGIVAL PLAQUE BY USING FLUORESCENT IN SITU HYBRIDIZATION (FISH) - Bhat, Kishore G.; Chhatre, Aradhana; Kumbar, Vijay M.; Kugaji, Manohar S.; Patil, Sanjeevani (International Journal of Research -GRANTHAALAYAH, 2017)
Motivation/Background: Red complex bacteria are proven periodontal pathogens. In dentistry, there is a need to identify and quantitate the organisms from the diseased sites quickly and reliably. Since culture requires several days, molecular methods are being used frequently to detect these bacteria. Among them, Fluorescent in situ hybridization (FISH) is rapid, sensitive and quantitative. An attempt is made here to evaluate the applicability of this technique as a diagnostic tool in periodontology. Method: Subgingival plaque was collected from participants, fixed with paraformaldehyde and subjected to FISH. Fluorescently labeled oligonucleotide probes were used for hybridization. After the procedure, the fluorescently stained bacteria were identified and counted from the smear and quantitated using a simple grading. Results: There was a significant difference in the prevalence and numbers of red complex bacteria in healthy and diseased subjects. A strong linear relationship existed between P. gingivalis, T. forsythia and T. denticola. Conclusions: The procedure used in the study is simple, rapid and can be easily adaptable. It also has a high sensitivity and has the ability to detect a single bacterial cell. The method can be directly applied to the clinical samples and can be used as a rapid diagnostic tool in periodontics.